Cell life and death in the anterior pituitary gland: role of oestrogens - Seilicovich, Adriana (2010)
Apoptotic processes play an important role in the maintenance of cell numbers in the anterior pituitary gland during physiological endocrine events. In this review, we summarise the regulation of apoptosis of anterior pituitary cells, particularly lactotrophs, somatotrophs and gonadotrophs, and analyse the possible mechanisms involved in oestrogen-induced apoptosis in anterior pituitary cells. Oestrogens exert apoptotic actions in several cell types and act as modulators of pituitary cell renewal, sensitising cells to both mitogenic and apoptotic signals. Local synthesis of growth factors and cytokines induced by oestradiol as well as changes in phenotypic features that enhance the responsiveness of anterior pituitary cells to pro-apoptotic factors may account for cyclical apoptotic activity in anterior pituitary cells during the oestrous cycle. Considering that tissue homeostasis results from a balance between cell proliferation and death and that mechanisms involved in apoptosis are tightly regulated, defects in cell death processes could have a considerable physiopathological impact.